PENGARUH KOMPETENSI GURU, KEPEMIMPINAN KEPALA SEKOLAH DAN SARANA PRASARANA MELALUI MOTIVASI KERJA TERHADAP KINERJA GURU - Setiawan, Okky; Cahyaningdyah, Dwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study investigates the effects of teacher competence, principal leadership, and school infrastructure on teacher performance, with work motivation serving as a mediating variable, in three public junior high schools in Batealit District. A quantitative causal design was applied using total sampling, involving 59 teachers who completed a Likert-scale questionnaire. Data were analyzed through SEM-PLS. All indicators met validity requirements, with loading factors between 0.701 and 0.876 and AVE values above 0.50 for Teacher Competence (0.607), Principal Leadership (0.635), Infrastructure (0.585), Work Motivation (0.614), and Teacher Performance (0.658). Reliability was exceptionally strong, supported by Cronbach’s Alpha values of 0.945–0.988 and Composite Reliability values of 0.950–0.988. The structural model shows that teacher competence (p = 0.183) and infrastructure (p = 0.201) do not directly influence teacher performance, whereas principal leadership has a significant direct impact (p = 0.005). Work motivation significantly affects teacher performance (p = 0.007) and is influenced by teacher competence (p = 0.029), principal leadership (p = 0.009), and infrastructure (p = 0.040). These three variables also demonstrate significant indirect effects on performance through work motivation, with p-values of 0.033, 0.044, and 0.048. The R² values of 0.612 for work motivation and 0.712 for teacher performance, together with a Q² value of 0.888, indicate strong predictive relevance. The study concludes that work motivation is the primary driver of teacher performance, while principal leadership is the most influential factor. Recommendations emphasize enhancing teacher motivation, strengthening competence development, improving leadership effectiveness, and upgrading infrastructure to support better performance.